Optimal Spectral Radiation Composition of a LED Phytolapm for Stimulating Carrot and Tomato Seed Development - A. A. Gubina; E. V. Levin; M. M. Romanovich; A. E. Degterev; N. O. Patokov; I. A. Lamkin; S. A. Tarasov (Известия высших учебных заведений России: Радиоэлектроника, 2022)
Introduction. Light-emitting diode (LED) irradiation is widely used in various spheres of human activity, including agriculture. Due to the growing urban population and aggravating environmental situation, the problem of high-quality food provision is increasingly attracting research attention. In this context, it is important to develop energy-efficient optical systems for ensuring optimal irradiation conditions for accelerating the growth of various types of plants and improving the quality of products in autonomous agro-industrial complexes.Aim. Determination of an optimal spectral radiation composition of a phytolamp consisting of LEDs based on AlGalnP (660 and 730 nm) and InGaN (440 nm), as well as phyto-LEDs (400. _ .800 nm), to stimulate the growth and development of tomato and carrot sprouts at the germination stage. Calculation of the LED optical power and photosynthetic photon flux density (PPFD).Materials and methods. Experiments were carried out to study the influence of visible radiation of different quality and quantity on the development parameters of carrot and tomato seeds, including germination energy, the appearance of cotyledon and primary leaves, seed germination, average hypocotyl and root length. Optimal spectral composition and radiation power parameters ensuring effective growth of plants were determined.Results. Additional 660-nm irradiation of tomato sprouts at the germination stage was shown to exhibit a positive effect on germination, average sprout length and root development. The best results of carrot germination and development were achieved when irradiated with short-wavelength light (PPFD 243 µmol∙s–1∙m–2). Irradiation of ~ 170 µmol∙s–1∙m–2 blue and 86 µmol∙s–1∙m–2 red light was found to be effective for enhancing carrot cultivation.Conclusion. The developed irradiation schemes can be used to vary the spectral radiation composition and PPFD at different stages of crop growth and development, thereby increasing yields and reducing energy costs. In the future, this technology can be used in space research, where high energy efficiency is fundamental.